2020
DOI: 10.1186/s13568-020-0948-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pullulanase production from recombinant Bacillus subtilis by optimization of feeding strategy and fermentation conditions

Abstract: Pullulanase is an important starch-debranching enzyme mostly used in starch processing-related food industries. However, the levels of pullulanase produced from recombinant Bacillus subtilis, a Generally Recognized as Safe (GRAS) host, are generally limited. To enhance the activity of pullulanase, batch fermentation and fed-batch fermentation were systematically investigated. The overall purpose is to improve the fermentation yield by optimizing the feeding strategy in the fermentation process, thereby increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…To account for potential biases between samples with uneven sequencing depth, all read counts from the remaining samples were rarefied to the read depth of the sample with the lowest read number. Specifically, bacterial and fungal communities in each sample were rarefied to 25,762 (the minimum number of bacterial sequences) and 68,080 sequences (the minimum number of fungal sequences), respectively (Glowska et al, 2020 ; Huang et al, 2020 ; Schloss & Handelsman, 2006 ); 154,572 valid bacterial sequences and 408,480 valid fungal sequences remained for subsequent analysis (Table A1 in Appendix 2). Illumina sequence analysis indicated 1,041 bacterial OTUs and 270 fungal OTUs with 97% similarity.…”
Section: Resultsmentioning
confidence: 99%
“…To account for potential biases between samples with uneven sequencing depth, all read counts from the remaining samples were rarefied to the read depth of the sample with the lowest read number. Specifically, bacterial and fungal communities in each sample were rarefied to 25,762 (the minimum number of bacterial sequences) and 68,080 sequences (the minimum number of fungal sequences), respectively (Glowska et al, 2020 ; Huang et al, 2020 ; Schloss & Handelsman, 2006 ); 154,572 valid bacterial sequences and 408,480 valid fungal sequences remained for subsequent analysis (Table A1 in Appendix 2). Illumina sequence analysis indicated 1,041 bacterial OTUs and 270 fungal OTUs with 97% similarity.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, various authors reported the enhanced production of pullulanase from recombinant Bacillus subtilis ( Zhang et al, 2020b ; Pang et al, 2020 ). Efficient enzyme and metabolite-producing strains produced by CRISPR engineering exist today, highlighting the technology’s enormous potential.…”
Section: Approaches Used To Increase Pullulanase Yieldmentioning
confidence: 99%
“…NM-DCM-1 ( Mesbah and Wiegel, 2018 ) and Lactobacillus plantarum L137 ( Kim et al, 2009 ) showed a comparable increase in enzymatic activity after the deletion of the non-conserved C-terminus. Zhang et al (2020b) also studied the susceptiblility to turn inactive at 50°C with a 50% reduction in its specific activity observed due to N-terminal truncation in case of pullulanase PulPB1. Another strategy of Structure/sequence-guided consensus has been proven, logically easier to create variations and mutant libraries that will promote enzyme-directed evolution and save time on experiments.…”
Section: Protein Engineering Of Pullulanasementioning
confidence: 99%
“…In line for various industrial and commercial applications of pullulan, its degradation and enzymatic conversion is highly required, so that variety of useful products could be obtained. However, this complex structure could only be broken down by specific glucanase amylolytic enzyme called pullulanase, a debranching enzyme ( Da Cruz, 2013 ; Zhang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Debranching enzymes are classified into indirect and direct branching enzymes. Amylo-1,6 glucosidases, indirect debranching enzymes produced by animals and yeast are only capable of hydrolysing a 1,6 - α branch point while pullulanases and isoamylases, classes of direct debranching enzymes found in plants and bacteria have been observed to effectively break α-1,6 glucosidic bond of unmodified substrate ( Hii et al., 2012 ; Zhang et al., 2020 ). Therefore, pullulanase (pullulan α-glucano hydrolase; EC 3.2.1.41) has been highly preferred in industrial processes because of its capability to be involved in saccharification of starch, amylopectin, pullulan and related polysaccharides in combination with other amylolytic enzymes and subsequently yield hydrolysis of α-1, 6 bonds in the polysaccharides with the production of maltose, maltotriose and fructose ( Wu et al., 2015 ; Ma et al., 2015 ; Dakhmouche et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%